Self-healing of early age cracks in cement-based materials by mineralization of carbonic anhydrase microorganism - Qian, Chunxiang; Chen, Huaicheng; Ren, Lifu; Luo, Mian (Frontiers in Microbiology, 2015)
This research investigated the self-healing potential of early age cracks in cement-based materials incorporating the bacteria which can produce carbonic anhydrase. Cement-based materials specimens were pre-cracked at the age of 7, 14, 28, 60 days to study the repair ability influenced by cracking time, the width of cracks were between 0.1 and 1.0 mm to study the healing rate influenced by width of cracks. The experimental results indicated that the bacteria showed excellent repairing ability to small cracks formed at early age of 7 days, cracks below 0.4 mm was almost completely closed. The repair effect reduced with the increasing of cracking age. Cracks width influenced self-healing effectiveness significantly. The transportation of CO2 and Ca2+ controlled the self-healing process. The computer simulation analyses revealed the self-healing process and mechanism of microbiologically precipitation induced by bacteria and the depth of precipitated CaCO3 could be predicted base on valid Ca2+.